An introduction to the theme issue - Zollman, Dean A.; Brown, Duncan (My University, 2016)
When the topic for the 2016 Gordon Research Conference (GRC) on physics research and education was selected in 2012, the timing seemed appropriate. Albert Einstein had explained in 1916 how his general theory of relativity predicted the existence of gravitational waves. Four years ago we could not have imagined that just a few months before this conference the detection of gravitational waves from the collision of two black holes would be announced. Thus, while the physics and education GRC is unique among Gordon Conferences, this one will be even more special in that it will be the first conference to bring together researchers and educators so shortly after a major discovery in the field. The increase in interest in fundamental science generated by this historic announcement is already evident, and the conference will provide a great opportunity to discuss better ways to teach students about relativity and gravitation.
Citation: Zollman, D. A., & Brown, D. (2016). An introduction to the theme issue. American Journal of Physics, 84(5), 325-326. doi:10.1119/1.4943960